Efficacy of intensity-modulated radiotherapy for resected thoracic esophageal squamous cell carcinoma - Zhang, Wencheng (Thorac Cancer, 2015)
BACKGROUND: Little is known about the clinical use of intensity-modulated radiotherapy (IMRT) in postoperative radiotherapy (PORT) of esophageal cancer; therefore, we retrospectively investigated the clinical value of postoperative IMRT among resected thoracic esophageal squamous cell carcinoma (TESCC) patients. METHODS: We enrolled a total of 228 patients with resected TESCC who underwent IMRT between January 2004 and June 2009 in the study. PORT was applied via IMRT with a median total dose of 60 Gy. The Kaplan–Meier method was used to calculate survival rates, and a log-rank test was used for univariate analysis. The Cox proportional model was used for multivariate analysis. RESULTS: The one, three, and five-year overall survival rates of all patients were 89.9%, 56.7%, and 45.1%, respectively. Univariate analysis showed that significant prognostic factors included Union for International Cancer Control 2002 stage, lymphatic metastasis, number of metastatic lymph nodes, the degree of metastatic lymph nodes, the degree of differentiation, and vascular tumor thrombus (P < 0.05). Treatment failure occurred in 98 (45.2%) patients because of recurrence or metastases. Early reactions were observed at rates of 18.0% for radiation esophagitis and 5.7% for radiation pneumonitis more than grade 2. Late side effects included anastomotic stenosis (1.3%) and gastrointestinal bleeding (3.1%). CONCLUSIONS: The postoperative prophylactic IMRT of TESCC provided a favorable local control rate and acceptable toxicity.